2019
DOI: 10.1128/aac.00309-19
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Trypanosoma cruzi Proteasome Inhibitors Using a Luminescence-Based High-Throughput Screening Assay

Abstract: Chagas’ disease, caused by the protozoan parasite Trypanosoma cruzi, is a potentially life-threatening condition that has become a global issue. Current treatment is limited to two medicines that require prolonged dosing and are associated with multiple side effects, which often lead to treatment discontinuation and failure. One way to address these shortcomings is through target-based drug discovery on validated T. cruzi protein targets. One such target is the proteasome, which plays a crucial role in protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Probably the most prominent recent development in Chagas disease drug research has been the increased use of high-throughput phenotypic screening [ 93 , 94 , 95 ]. The requirement for large compound libraries, robotic sample handling equipment, expertise in parasite biology, and over-arching funding mechanisms has brought together both the academic and commercial sectors, with not-for-profit drug development agencies, such as the DND i .…”
Section: Progress In Chagas Disease Drug Developmentmentioning
confidence: 99%
“…Probably the most prominent recent development in Chagas disease drug research has been the increased use of high-throughput phenotypic screening [ 93 , 94 , 95 ]. The requirement for large compound libraries, robotic sample handling equipment, expertise in parasite biology, and over-arching funding mechanisms has brought together both the academic and commercial sectors, with not-for-profit drug development agencies, such as the DND i .…”
Section: Progress In Chagas Disease Drug Developmentmentioning
confidence: 99%
“…The vinylsulfone 125 I-NP-L2N-VS, labels exclusively the β2 subunit of T. brucei , but both β2 and β5 of human origin ( Wang et al, 2003 ). Furthermore, the peptide suc-Leu-Leu-Val-Tyr-AMC is cleaved exclusively by β5 in human proteasomes, but by β5 and β1 or β2 in the T. brucei proteasome ( Zmuda et al, 2019 ).…”
Section: The Ubiquitin-proteasome Systemmentioning
confidence: 99%
“…These include various peptide aldehydes, epoxomicin and its derivatives, peptidyl vinyl sulfones, peptidyl vinyl esters, and several natural γ-lactam-β-lactones ( Glenn et al, 2004 ; Steverding et al, 2005 ; Steverding et al, 2011a ; Steverding et al, 2011b ). Several studies have shown differences in the relative inhibition of β5 and β2 subunits between trypanosoma and human proteasomes, again indicative of the parasite proteasome possessing distinct catalytic activities ( Nkemgu-Njinkeng et al, 2002 ; Wang et al, 2003 ; Zmuda et al, 2019 ). However, the design or selection of trypanosomatid-selective inhibitors based on these proteolytic differences has not yet been possible ( Steverding et al, 2018 ).…”
Section: Inhibition Of the Proteasomementioning
confidence: 99%
See 1 more Smart Citation
“…GNF6702 was invented by researchers working at the Genomics Institute of The Novartis Research Foundation in 2013, with activity against these diseases. Another inhibitor, the GSK3494245/DDD01305143, is a preclinical candidate for visceral leishmaniasis developed from a T. cruzi screening hit [ 50 , 51 , 52 , 53 ]. Recently, new T. cruzi proteasome inhibitors using a luminescence-based high throughput screening assay have been identified [ 52 ].…”
Section: Drugs Targets and Inhibitorsmentioning
confidence: 99%